Locational and Seasonal Bioaccumulation of Heavy Metals in Bivalves Sinanodonta woodiana and Unio tigridis from the Al-massab alam River, Thi-qar province - M. Al-taher, Qasim (Technium BioChemMed, 2024)
The aim of this research was to measure and compare the contents of three elements (chromium, uranium, and aluminum) in water, sediments, and oysters (Unio tigridis and Sinanodonta woodiana) from three stations in different seasons. The results showed that the concentration of these elements varied widely while exhibiting some trends and patterns. Chromium had very low concentration in water as well as oysters yet there was an increase in sediments during winter until autumn. Uranium had low concentrations in water plus oysters however its concentration increased significantly during summer including autumn season in water as well as sediments. Aluminum exhibited wide variations among stations and seasons with no clear trend or pattern both in water, sediments and oysters. Several factors might have caused variations of these elements such as; natural geochemical background, anthropogenic activities, hydrological conditions, biological processes and analytical methods used. It is therefore necessary to conduct more research on these variations so that their causes could be identified as well as their effects while assessing the potential ecologic impacts plus human health risks within the study area.